PENGARUH DAMPAK PEMBIAYAAN BANK KALBAR SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI KALIMANTAN BARAT PERIODE TAHUN 2010 - 2020 - Barata, Juliahir; S, Yuana (Jurnal Ekonomi Integra, 2024)
The purpose of this study was to determine the effect of Bank Kalbar Syariah Financing on economic growth in West Kalimantan. The data used in this study is time series data in the form of Economic Growth (%) sourced from the Central Statistics Agency, Financing (million rupiah), ROA (%), total assets (million rupiah) and FDR (%) from 2010-2020 sourced from the Annual Report of Bank Kalbar and Monthly Publications of Bank Kalbar Syariah. The results of this study can be said that ROA has a negative and insignificant effect on the financing of Bank Kalbar Syariah. FDR and total assets have a positive and significant impact on the financing of Bank Kalbar Syariah. Financing has a negative and insignificant effect on West Kalimantan's economic growth, while ROA, FDR and Total Assets have a positive and insignificant effect on West Kalimantan's economic growth.